Cellular Bone Matrix Leading to Disseminated Tuberculosis After Spinal Fusion: A Report of 2 Cases. Issue 2 (24th April 2023) - Issa, Tariq Z.; Lambrechts, Mark J.; Toci, Gregory R.; D'Antonio, Nicholas D.; Kanhere, Arun P.; Lingenfelter, Kenneth; Schroeder, Gregory D.; Vaccaro, Alexander R.
Abstract : Case: Although implanted tuberculosis (TB) is rare, a single lot of cellular bone matrix was found to be infected with TB, leading to devastating outcomes. We present 2 cases referred to our institution because of instrumentation failure caused by TB inoculation of cellular bone matrix. Conclusion: Irrespective of spinal region of implanted TB infection, excision of infected bone, extensive irrigation and debridement, and instrumented stabilization are of primary importance to ensure TB eradication and adequate stabilization.